Kajian Sistem Pemberian Air Irigasi Sebagai Dasar Penyusunan Jadwal Rotasi Pada Daerah Irigasi Tumpang Kabupaten Malang - Huda, M. Nurul; Harisuseno, Donny; Priyantoro, Dwi (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2012)
Tumpang Irrigation Area of Kabupaten Malang with irrigation area 614 Ha as facility to support Government Programs in producing 10 million ton rice surplus in 2014. Evaluation of existing condition is realization of rice and crop planting intensity is 204%. Evaluation of water availability is using K factor that is K ï‚³ 1. Planning in replanting design by increasing paddy planting intensity is using two water distribution system, that is SCH method (stagnant content head) and SRI method (system rice of intensification). By increasing paddy planting intensity into 245%, rotation event in irrigation water distribution by Qmodus and Qminimum is using more of SCH method than SRI method. Paddy water needs in one year planting period by SRI method is 28% cost-effective than SCH method.Keywords: evaluation, planting intensity, SCH method, SRI method, rotation.